AN ANALYSIS OF ENGLISH TEXTBOOK FOR FIRST GRADERS OF SENIOR HIGH SCHOOL “BAHASA INGGRIS UNTUK SMA/MA DAN SMK/MAK KELAS X” PUBLISHED BY PUTRA NUGRAHA AND USED IN SMAN 18 SURABAYA BASED ON BASIC COMPETENCES OF CURRICULUM 2013 (RETAIN, 2014)
AGREEMENT SHEET This is to certify that the Journal with the title “AN ANALYSIS OF ENGLISH TEXTBOOK FOR FIRST GRADERS OF SENIOR HIGH SCHOOL “BAHASA INGGRIS UNTUK SMA/MA DAN SMK/MAK KELAS X” PUBLISHED BY PUTRA NUGRAHA AND USED IN SMAN 18 SURABAYA BASED ON BASIC COMPETENCES OF CURRICULUM 2013” written by ABU DARRIN (NIM.102084005) has been thoroughly checked and fulfilled the requirements for Yudisium. Surabaya, January 2014 Advisor Drs. Fahri, M.A. NIP. 19640819 199003 1 003 AN ANALYSIS OF ENGLISH TEXTBOOK FOR FIRST GRADERS OF SENIOR HIGH SCHOOL “BAHASA INGGRIS UNTUK SMA/MA DAN SMK/MAK KELAS X” PUBLISHED BY PUTRA NUGRAHA AND USED IN SMAN 18 SURABAYA BASED ON BASIC COMPETENCES OF CURRICULUM 2013 Abu Darrin English Education Department, Language and Art Faculty, Surabaya State University Email: abudarrin92@gmail.com Drs. Fahri, M.A. English Education Department, Language and Art Faculty, Surabaya State University. Email: fahri@unesa.ac.id Abstrak Kurikulum adalah sebuah alat untuk mengontrol implementasi dari pendidikan di semua negara tidak terkecuali Indonesia. Di tahun 2013, pemerintah Indonesia telah menerbitkan kurikulum yang baru yaitu kurikulum 2013. Kurikulum ini diklaim dapat meningkatkan kualitas pendidikan di Indonesia. Berkaitan dengan pentingnya hal tersebut, kesesuain antara materi di dalam buku pelajaran dengan kompetensi dasar di dalam kurikulum 2013 juga sangatlah penting. Hal ini juga didukung oleh fakta bahwa kebanyakan guru menggunakan buku pelajaran sebagai sumber utama pengajaran di dalam kelas karena pelatihan guru tentang kurikulum baru ini masih minim sekali. Penelitian ini dilakukan untuk mengetahui apakah komtensi dasar di dalam buku pelajaran dengan judul “Bahasa Inggris Untuk SMA/MA dan SMK/MAK Kelas X” yang diterbitkan oleh Putra Nugraha sesuai dengan kompetensi dasar yang tercantum di dalam silabus bahasa inggris kurikulum 2013. Selain itu, penelitian ini juga dilakukan untuk mengetaui dan mendeskripsikan materi-materi apa saja di dalam buku pelajaran tersebut diatas yang sesuai dengan kompetensi dasar di dalam silabus kurikulum 2013. Dengan menggunakan konsep deskriptif kualitatif, penelitian ini menggunakan field notes yang diadaptasi dari garis besar evaluasi buku pelajaran di dalam BSNP (Badan Standar Nasional Pendidikan). Materi di dalam buku pelajaran ini dianggap sesui apabila telah memenuhi indikator materi urutan dari kompetensi dasar kurikulum 2013. Dari hasil penelitian, dapat diketahui bahwa semua kompetensi dasar di dalam buku pelajaran sesuai dengan kompetensi dasar di dalam silabus kurikulum 2013. Selain itu, diketahui juga bahwa kebanyak materi di dalam buku pelajaran tersebut tidak sesuai dengan kompetensi dasar di dalam silabus kurikulum 2013. Materi yang sesuai antara lain adalan materi di dalam bab 1, 2, 3, 5 dan 7. Ketidaksesuain tersebut kebanyakan disebabkan oleh ketidaksesuaian urutan materi di dalam buku pelajaran dengan kompetensi dasar kurikulum 2013.Kata Kunci: Buku Pelajaran Bahasa Inggris, Kompetensi Dasar kurikulum 2013, kesesuaian. Abstract Curriculum is a tool to control the implementation of education in the country including Indonesia. In 2013, the Indonesian government has issued a new curriculum, namely, curriculum 2013. It is claimed as improving the education in Indonesia. Since it is very important, the conformity between the materials in the textbook to the 2013 English basic competence is also taking a vital role in implementing this new curriculum. It is supported by the fact that mostly the teachers uses textbook to deliver the material in the class because they are not well introduced yet to it. This research is conducted to figure out whether the basic competences in the textbook entitled “Bahasa Inggris Untuk SMA/MA dan SMK/MAK Kelas X” published by Putra Nugraha conform to the basic competences in the syllabus of English curriculum 2013 or not. Besides, this also figure out whether the materials in the textbook entitled “Bahasa Inggris Untuk SMA/MA dan SMK/MAK Kelas X” published by Putra Nugraha conform to the basic competences in the syllabus of English curriculum 2013 or not. By employing the concept of descriptive qualitative study, this research uses the field notes which are adapted from BSNP textbook evaluation guideline as the research instrument. The textbook is claimed as representing the basic competence of the syllabus in the curriculum if the materials completely conform to the basic competences and its sequence. The results of this study show that all of the basic competences in the textbook conform to the basic competences for first graders of Senior High School in the first semester syllabus of English curriculum 2013. Besides, it also shows that most of the materials in the textbook do not conform to the basic competences in the syllabus of English curriculum 2013. Few of the relevant materials are there in chapter 1, 2, 3, 5 and 7. In addition, most of the inconformity of the materials in the textbook is because they are not in the right sequence as mentioned in the Syllabus of English curriculum 2013. Key Words: English textbook, 2013 English basic competences, conformity. INTRODUCTION Students of all ages are learning to speak English all around the world (Harmer 2007). That is the evidence of the fact that English is the most popular International language used in the world. This language is used as a tool to transfer many kind of information from the others language. It is used to communicate importantly when the people do not know the certain unpopular international or even non international language. For the example; Indonesian that would like to communicate with Japanese, in case, both of them cannot speak Indonesian or Japanese, they can use English. It is rationally because English is the popular international language that mostly used by the people around the world both, in target language community or even in somewhere it is one of the main languages of culture or commerce. Target-language community is a place where English is used as the national language- e.g. Britain, Canada, New Zealand, etc. besides, India, Pakistan, Nigeria are the example of the countries where English is one of the main languages of culture and commerce (Harmer 2007). Those examples show us that English has widely used almost all around the world referring to the fact that the origin of English is from Germany. Besides, people can take a look on the point of view of education field and work field. English as a subject taught in school and college deals with the student’s understanding and use of language (Guth 1973). Furthermore, the transfer of information and knowledge has been easily accessed whenever and wherever, seems there is not any limitation of time and place anymore. As the example, people can easily get the information from social media or internet. As long as they could use English to communicate, they could keep in touch with whoever or whatever around the world. As the concrete example, the student could use international references in doing their project or research. Moreover, it is not surprising news anymore knowing the transfer of the students around the world. According to the fact, it seems like not enough to study in the country for the specific purposes of certain people. They would rather choose to continue their study abroad than in their own country. This opportunity leads to make the use of English being more and more important than the other foreign language. Looking to another point of view, the use of English essentially spreads widely in the international business sector, so much so that English has become the standard language of world business (Yoneda 2008). Relating to the development of some international development, the use of English is also getting more important. For the example is the implementation of ASEAN Economic Community (AEC) in 2014. This agreement among ASEAN countries about free economic market in ASEAN open a new opportunity for every people in ASEAN countries to work in certain country in ASEAN (Community 2008). This also shows us that the role of English is very fundamental according to the fact that the countries in ASEAN have their own language. English as international language relates the people of ASEAN to communicate each other, so that there are not any difficulties anymore in term of communication of those different language countries. In addition, we can easily find the requirements of job field in our country that requires English whether written or oral skill to fulfill. In this circumstance, English also take a great importance in human social life even though it is not in English-native speaker country. Those great importance of English in daily life of the society and its prospect in the future lead the governance to put English as a major material begin in junior high school and senior high school. As the higher continuant education, senior high school has a significant role to build the extensive foundation of the student competence of English after the very basic level in elementary and junior high school. In this level, English is delivered more seriously and being a component of the syllabus of curriculum in Indonesia as stated in constitution of Indonesia number 68 2013. This curriculum has been launched in 2013. It has been used and being implemented in certain school all around Indonesia starts from the first class of junior and also senior high school. This curriculum was built based on two major challenges. Those are internal and external challenges (Permendikbud 2013a). The internal challenge is that the human resources of Indonesia are getting large and large. As the response of the government, the curriculum 2013 was build to increase the competence of the people itself. Furthermore, the global change and development are acting as the external challenge that encourages the development and the existence of curriculum 2013. The curriculum 2013 actually is developed from standard-based curriculum and competence based curriculum, that is why, the difference between this curriculum and the previous curriculum can be clearly seen from the format of the curriculum itself. In the other hand, textbook is getting a great role in education related with the implementation of the curriculum (Permendikbud 2013b). It is also supported by the fact that nowadays, there is a change of education paradigm. Begin with teacher as a center in learning in the class to the students as the center in the class. That is why, textbook as the main source of knowledge which is stated in the curriculum besides the teacher is holding a fundamental role in the education. A little bit different with the previous curriculum, especially in English object, the curriculum 2013 uses thematic approach. Based on the English textbook published by Putra Nugraha entitled “Bahasa Inggris Untuk SMA/MA dan SMK/MAK Kelas X”, there is not any skill dividing such as in the English textbook of the previous curriculum. The skill such as listening, reading, writing and speaking are no longer used to divide the competences in the textbook. It uses the thematic approach that integrates those kinds of skill to be one competence. Those differences lead the researcher to figure out a problem, does the content of the textbook really conform to the content of the syllabus of curriculum 2013?. In addition, this textbook is published in 2013 and used in SMAN 18 Surabaya. It is the only one which is found in the field. Even though the English curriculum 2013 has been implemented, only SMAN 18 Surabaya that uses the English textbook to deliver the English material. The gap exists in the previous study also supports the researcher to conduct the research to answer the question. There are a lot of researches about textbook analysis of previous curriculum textbook such as a research conducted by the graduate of state University of Surabaya. The title is “An Analysis of Listening Material of English Textbook Entitled Get Along With English for Vocational High School Grade X Based on 2006 English Standard Competence” (Widiyawati 2012). This descriptive qualitative research is conducted to evaluate the book in the point of listening skill competence based on the 2006 English Standard Based Competence. The researcher take the Listening skill as the competence to be evaluated in the book because, in fact the book was made based on curriculum 2006 that still uses skill competence to divide the material in the book. Another one is a research conducted by Meta Chairani (2011) the graduate of Muria Kudus University entitled “The Analysis of English Textbook based on Competence Based Curriculum (CBC) for The First Year of Senior High School Published by Penerbit Erlangga and PT. Intan Pariwara. This research also analyzes the textbook of previous curriculum that is Competence Based Curriculum (CBC). So far, none of the researchers conduct a research of the textbook of curriculum 2013 that has been implemented since 2013. Recognizing this gap and urgency that it is a must for the content of the English textbook to conform with the Syllabus of the curriculum 2013, the researcher is supported to conduct this research. In addition, the researcher will use the instrument based on Badan Nasional Standart Pendidikan (BSNP) with also referring to another theory. This is to check the conformity between the basic competences in the syllabus of curriculum 2013 and the basic competences in the textbook and also the conformity between the materials in the English textbook to the basic competences in the syllabus of curriculum 2013. Based on the background and the reason above, it shows that conformity between the book and the basic competence is an urgent and important thing in the implementation of curriculum 2013. Based on the Background above, the researcher decide to research questions of this study are: How is the conformity between the basic competences in the English textbook for first graders of senior high school used in SMAN 18 Surabaya entitled “Bahasa Inggris Untuk SMA/MA dan SMK/MAK Kelas X” published by Putra Nugraha and the basic competences in the syllabus of curriculum 2013? And How is the conformity between the materials in the English textbook for first graders of senior high school used in SMAN 18 Surabaya entitled “Bahasa Inggris Untuk SMA/MA dan SMK/MAK Kelas X” published by Putra Nugraha and the basic competences in the syllabus of curriculum 2013? The result of this study is expected to give more information and input to the teacher in using the English textbook entitled “Bahasa Inggris Untuk SMA/MA dan SMK/MAK Kelas X”. It is expected to give them a brief overview of the textbook, so that they would know the appropriate use of it, whether they have to add some material of the syllabus that does not exist in the textbook or even skip some contents in the textbook that does not included in the syllabus of curriculum 2013. Furthermore, this research is also introduced to the writer and the editor of the textbook in order to give them input and guideline in making the next English textbook which is more relevant to the curriculum 2013. In addition, the researcher focuses on the English textbook for the first grade of senior high school entitled “Bahasa Inggris Untuk SMA/MA dan SMK/MAK Kelas X” used in SMAN 18 Surabaya only to check the conformity of it to the basic competences of the syllabus of curriculum 2013. REVIEW LITERATURE Curriculum is a set of planning and setting of the objectives, contents, and the material of the teaching and learning process that is used as a guideline in realization of the teaching to achieve the goal of the certain education (UU No. 20 Th. 2003 Tentang Sistem Pendidikan Nasional). Besides, Tanner (1980) defined curriculum as “the planned and guided learning experiences and intended outcomes, formulated through the systematic reconstruction of knowledge and experiences under the auspices of the school, for the learners’ continuous and willful growth in personal social competence”. It is used to develop and increase the even distribution of education. Every country usually has each own standard of the curriculum because it is related with the development of the country itself. Besides, it also depends on the students’ needs in the each country. Since it depends on the students needs the curriculum always having the improvement time by time. It is caused by the global change that occur influence the needs of the learner. In case of English curriculum, there have been some changes or improvement of it in Indonesia. The changes are stated as follows: Old style, Grammar Translation Based Curriculum (1945), New Style, Audio Lingual Based Curriculum (1958), Revision, Audio Lingual Based Curriculum (1975), Structure Based Curriculum (1984), Communicative Based Curriculum (1994), Competency Based Curriculum (2004), Unit Level in Education Curriculum (2006) and Integrated English Curriculum (2013). The most recent curriculum is curriculum 2013 that has been launched in 2013. The English curriculum in it is no longer using skill as the point to divide the competence. It is integrated and thematic. Furthermore, Curriculum 2013 has been launched by the ministry of education and culture of Indonesia in more than 6000 schools all around Indonesia. This is the next step of the ministry of education and culture after holding some process- target teacher and instructor teacher training about curriculum 2013 (Sutiana 2013). Actually, the main substance of curriculum 2013 is the review of internal factors as a demand of education that refers to the 8 national education standards. Those include the management standard, expense standard, infrastructure standard, teacher standard, content standard, assessment standard and the competence standard of the alumnus. The other internal challenges are related with the development of Indonesia from the citizen productive age point of view (in 2020-2035 the productive age is abundant). Besides, the external challenge is also taking a role, the demand of the globalization that comes up with certain goals to achieve through future competence. Those are; communication competence, critical thinking competence, the competency to see the moral values of the problem, ready to work and the ability to live in global society, and etc (Permendikbud 2013a). So far, the global challenge in the society, especially in the future of work field that soon will be globalized, is the basic philosophical framework of this curriculum beside the past and the current condition of Indonesia. Those three values of point of view are taken to build the strength of the mental thinking of Indonesian to face the globalization above. Since the implementation of this curriculum is step by step, it is implemented in the first grade of junior high school. Based on the basic framework of this curriculum from the ministry of education and culture of Indonesia the description of English curriculum is something like the explanation as follows (Sutiana 2013). As stated in the constitution, there is a significant change in this curriculum 2013. That is the graduate standard competence or “standart kompetensi lulusan (SKL)” that related with all of the subjects. It means that the implementation of all subjects must refer to the standard. In the other side, the graduate standard competence itself is depending on the student’s needs in the future that focusing on the balance soft skills and hard skills. Furthermore, the main competence is related with the basic competence that exists in every subject. In addition, the text distributing that will be the content in the linguistic material are:Interpersonal Text, Private expression such as greeting and the responds, leave taking and the responds, thanks giving and the responds, and apologizing and the responds; Transactional Text, asking and giving the information about the fact and feeling and also offering things and service; Special Functional Text, such as: name label, List (list of thing in one group), instruction, sign or traffic light, warning sign and song; Public Functional Text, such as: names of the day, month, time in a day, time in form of number, dates and years, self introduction, names of animal, things and public building, the characteristic of human, animal and things. The attitude/action/function of human/animal/things. Descriptive (human, things, and animal); Conversation Topic: related with human self and the social and natural environment around the house and school. Teaching process in curriculum 2013 using scientific approach, through some steps of the process: observing: the student read/watch/listen to the examples of texts that is being learned from many kind of sources, directly/ or using a recording that concerning to the social function, text structure, linguistic element or the delivery format or the writer; asking : through questions from the teacher, the students are asking many things based on the topic/ teaching material, such as social function, expression and text structure and etc; Exploration/ experiment : reading/watching/ listening the other examples of the text they learn; associating/analyzing : in an under control group work, the students are learning to mention the social function, expression and text structure, linguistic element, and the writing format of the type of text they learn. The feedback from the teacher and students in every result of group work are delivered. The last is, communicating: reading, listening, presenting/publishing/ speaking/reading the text they learn. In the other hand, 2006 English curriculum is unit level in education curriculum (KTSP). In this curriculum, each school in Indonesia has each own authority to develop the material based on the students’ needs (Nahrowi 2013). Furthermore, this curriculum also concern on the skills as the point to deliver the competences in English such as listening, speaking, reading, and writing. It is completely different with the curriculum 2013. The government standardizes the curriculum as the same one for every school. It means that there is not any differences for every school in Indonesia, in fact, the condition of schools are different each other. Besides, the curriculum 2006 divides the competences into several point based on the skills. Then, The curriculum 2013 is integrated (Nahrowi 2013). This difference of course is included as a significant difference that also could significantly differentiate the previous textbook of the curriculum to the textbook of curriculum 2013. The textbook of curriculum 2013 is no longer divided based on the skill competence, but it is divided based on the theme as shown in the textbook of curriculum 2013 published by Putra Nugraha entitled “Bahasa Inggris Untuk SMA/MA dan SMK/MAK Kelas X”. Textbook is used as a main guideline in language teaching especially where the teacher is least capable to deliver the material, but the fact said that not all the textbook can reflect the materials well (Williams 1983). This situation of also happens in Indonesia where the EFL classrooms are applied. Furthermore, the existence of the textbook also causes some questions. What the textbook actually is, what advantages of disadvantages of the textbook are, how to create the textbook, how to evaluate it, and also, the most important is, what the relationship between the textbook and the curriculum actually is. Textbook generally is a book contains some material of certain subject to learn by the students in the school. It is used as a main component to deliver the material framework designed in the curriculum. They may deliver the foundation for the content of the lessons, the balance of skills taught and the types of language practice the students take part in. In other hand, the textbook may provide primarily to supplement the teacher's instruction (Richards 2013). Besides, sauvignon (1983) stated that textbook contains a collection of written or oral texts with accompanying explanations that are selected and sequenced for the learners as cited in the previous study (Widiyawati 2012). As the definition above, we can see that actually, textbook can varies based on the language teaching stakeholders. It can adapt the curriculum, the teacher needs, and also the students’ needs. That is why, we can find a different textbook used in a different schools. This chosen textbook is used as a basic guideline in teaching and learning process. It is stack because the teacher should follows the curriculum framework designed by the government beside they could adjust their needs. This textbook is very helpful because it contains the material instruction for the teacher that also can support the students to learn by themselves whenever and wherever they want. The material instructions usually could be varied as the curriculum framework. It could be in form of oral or written text, sounds for listening in form of CD that is very practice to use. The existence of the textbook is very crucial in language teaching. It has so many advantages to support the language learning and teaching process, but as the creation of human being, it also has some disadvantages. As the evidence, the textbook evaluation and its revision always applied time by time. The advantages and the advantages of the commercial textbook also depends on the how they are used and the contextual factors and the advantages are stated as (Richards 2013): It is providing structure and a syllabus for a program. Without textbooks a program may have no central core and learners may not receive the material as stated in the syllabus that has been systematically planned and developed by the government; It is helping standardize instruction. The textbook helps the government to implement the even distribution of the education by the similarity of the material taught in each school or even in each class; It is maintaining quality. If a good textbook is used, students are exposed to a tried and tested, that are based on certain pointed learning principles, and that are skipped appropriately; It is providing a variety of learning resources. Textbooks are usually accompanied by workbooks, CDs and cassettes, videos, CD ROMs, and comprehensive teaching guides, providing great resource for teachers and learners; It is efficient. The textbook save teachers' time, enabling teachers to devote time to teaching rather than material's delivering; It is providing effective language models and input. Textbooks can provide supports for non-native teachers and who may not be able to produce accurate language input on their own; They can train teachers. It can be a medium of initial teacher training or a limited teaching experience teacher; It is usually appealing. Commercial textbooks usually have high standards of design and production and hence are appealing to learners and teachers. Contradictory to that, the potential negative effects of the use of textbooks are: It may contain inauthentic language. Textbooks in some cases present inauthentic language since texts, dialogs and other aspects of content tend to be specially written to incorporate teaching points and are often not representing real language use; It may distort content. Textbooks often deliver an idealized view of the world or fail to represent real issues. In order to make fail represented view of material, controversial topics are avoided; It may not reflect students' needs. Textbook are produced in mass amount. That is why; usually the textbook doesn’t match the certain needs of the students; It can deskill teachers. If the teacher just use the textbook as an over dominant centered, it can de skill the teacher. It occurs when the teacher is not having improvement in experiencing the class; It is expensive. Commercial textbook that is usually expensive can burden the students in low financial level; Those advantages and advantages gives the redline review for the teacher. If the disadvantages side of the textbook takes a dominant position in the class. The alternative action should be taken, such as adding some materials if there are some of them do not exist in the textbook and etc. Furthermore, what does differentiate the previous textbook curriculum and the textbook of curriculum 2013 especially in language teaching is the approach. The previous curriculum divide each skill competences in the material delivery, but, significantly different to that, the curriculum 2013 use an integrated approach that divide the material into several theme. This is considered more effective in language teaching just like the idea of Oxford (2001) that stated, the integrated approach in foreign language teaching must focus on the integration of language elements like vocabulary, pronunciation and the structure that support the language skill (sundayana 2013). Those two significance differences lead to the textbook construction difference. The textbook of previous curriculum uses the skill in dividing the material in the textbook, they divide listening, speaking, reading, and writing in every material. For the example, descriptive text teaching that is delivered by listening to the descriptive text sound, descriptive speech, descriptive reading, and descriptive writing. Different to that, based on the curriculum 2013framework that has been explained above, the textbook of English curriculum 2013 is constructed by referring to the basic competence in the syllabus. It is constructed as an integrated language material that integrates all language skill such as listening, speaking, reading, and writing into one thematic material. For the example, the language teaching in the first grade of senior high school with the theme “I am going to…”. In this theme the material is given to lead the students to explore their language skill. By this theme, the teacher indirectly teaches listening, speaking, reading, and writing in the same time. In condition where there it is lack of trained Teacher, textbook has a vital position in language teaching (Williams 1983). This statement also strengthens the urgency of a well evaluated textbook because of the importance of the existence of textbook itself in the language teaching. The criteria of evaluating the textbook is also take a big role in defining and evaluating the textbook for the betterment of the language teaching. The criteria to build the instrument should be relevant and based on the trusted sources. Since it is important, this evaluation of the textbook should be done especially for the stakeholder of the teacher. The teacher could be given some practices in evaluating the textbook in order to figure out whether the organization of materials is consistent with the objectives of given English curriculum (Williams 1983). The statement of this English education scientist indirectly also shows us that the consistency between the objectives of given English curriculum and the organization of materials is holding an important urgency in the English language teaching. This could be the foundation in making an instrument to define an appropriate textbook based on the curriculum. Besides, there is a valid instrument for evaluating the textbook, including English textbook for senior high school. This instrument that is made by BSNP (Badan Standard Nasional Pendidikan) contains some components of textbook which are arranged based on characteristic of English learning and the criteria of English textbook development (Widiyawati 2012) . The textbook evaluation instrument made by BSNP consists of three main components; the feasibility of the content of the evaluated textbook, the feasibility of the language use of the evaluated textbook, and the feasibility of the presentation of the evaluated textbook. Furthermore, there are sub-components for each component of this evaluation instrument (BSNP 2007), they are: the feasibility of the content of the evaluated textbook; The feasibility of the language use of the evaluated textbook; the feasibility of the presentation of the evaluated textbook. Curriculum is a fundamental substance in the educational system. It drives how the education would look like and it controls the whole unit of education. For the betterment of education in Indonesia for example, the governance does not just revise improve the front liner of education here is the teacher, the facility, and the maintenance but also, the regular revision of curriculum. This fact leads us to understand that the basic change of education improvement is led by the curriculum. In addition, the recent curriculum has taken a serious focus on the equality of education. The equality of education support the potential talent (Rajakumar 2006). It is also reflected by this new policy of education that equal all the material for all school implemented with the standardized standard competence. This basic competence is the main reflection of the curriculum 2013 itself. All of the material guidelines are stated in this standard competence. Furthermore, as the competition of this new curriculum implementation, the teacher mostly uses the textbook as the main material in English teaching. It is caused by the less trained teacher that wants to give the most appropriate material based on the curriculum. Moreover, the well trained teacher uses the textbook as well as the main guideline based on many kind of reason. This idea is strengthen by the language researcher that stated “They can be given practice in analyzing textbooks in order to find out whether the organization of materials is consistent with the objectives of a given English language curriculum” (Williams 1983). Form this view, it can be seen that the role of appropriate textbook of curriculum 2013 is very fundamental and indirectly it also shows that their relationship is very close and can’t be divided each other. There have been some previous studies about the textbook analysis, and some of them found that in certain point, there are irrelevancies between the textbook and the goals of English teaching as included in the curriculum. Those findings are clearly proves that the textbook used by school as a teaching guideline has a possibility to have the irrelevancy between the curriculum and the materials in the textbook itself. As the first example, a research conducted by a graduate of State University of Surabaya have found that there are some speaking indicators that are not covered in each unit of the textbook entitled “ Mandiri: Practice your English Competence”. For example, two indicators of basic competence 2.4 in Chapter 3; and two indicators of basic competence 2.3 in Chapter 6 (Xingli 2013). The second research is also conducted by the graduate of State University of Surabaya. Several text in the textbook entitled “kumpulan kegiatan siswa Bahasa Inggris” designed by Surabaya MGMP team have not fulfilled yet the requirement of the generic structures and the linguistic features yet as stated in 2004 English Curriculum (Sari 2007). Then, the last example of research is conducted by Meta Chairani, the undergraduate of Muria Kudus University (UMK) entitled “The Analysis of English textbook Based on Competence based Curriculum (CBC) for the First Year of Senior Higfh School Published by penerbit Erlangga and PT. Intan Pariwara. Different with the two previous research example, this research was comparing two different textbook to know which one is more appropriate to the curriculum. The result of this study is both of the textbook are fairly good, but only the book of PT. Intan Pariwara entitled “Bahasa Inggris Kelas 1 SMU” was appropriate in content and evaluation to cover the objective of Competence Based Curriculum (Chairani 2011). So far, based on the examples of researches above, it has been clearly found that there are some irrelevance between the textbook and the curriculum starts from Competence Based Curriculum (CBC) that was implemented since 2004 to 2006, and the Unit Level of Education Curriculum (KTSP) that was implemented in 2006 to 2013. This kind of evidences shows us that there is a big possibility of the textbook published by the Government that does not match with the curriculum in certain point. Of course, it is included the textbook entitled “Bahasa Inggris Untuk SMA/MA dan SMK/MAK Kelas X” published by Putra Nugraha as a guideline to implement the Curriculum 2013. This is the main reason why the researcher would like to conduct this study. RESEARCH METHODOLOGY Research Design This study is designed to answer the research question as stated in the Chapter I. It focuses on analyzing the conformity of the material in English textbook entitled “Bahasa Inggris Untuk SMA/MA dan SMK/MAK Kelas X” published by Putra Nugraha to the basic competencies in the syllabus of curriculum 2013. This English textbook is used by SMAN 18 Surabaya in the first year of curriculum 2013 implementation. Based on the objectives and the aim of the study above, this research is designed to analyze the English textbook that has been a phenomenon. Until nowadays, there is not any legal curriculum 2013 English textbook for senior high school published by the government. Since this study is descriptive qualitative research, the analysis of the study is presented in form of words rather than numbers without any statistical calculation (Fraenkel JR & Wallen, NE 1990; McMillan (as cited in Widiyawati 2012). Besides, this study is also documentary analysis research in which it describes the data gotten from the research instrument in detail and deeply. Object of the Study The Subject of this study is the English textbook for the first graders of Senior High School entitled “Bahasa Inggris Untuk SMA/MA dan SMK/MAK Kelas X” published by Putra Nugraha. It was published in 2013. The materials in the textbook are organized in form of chapter in which the four skills of English such as Listening, Speaking, Reading, and writing are integrated to be one thematic chapter. There are seven chapters that cover one semester material, they are: I Live in Semarang, Wow! You Look So Pretty! , Are You Ok? , I’m Going to…, Congratulations, Simple Past Tense and Simple Present Perfect Tense, Descriptive Text. As stated above, those themes provide integrated English materials that also integrate the four skills of English. Data of the Study The data of this study are all of the English learning material presented in this textbook entitled “Bahasa Inggris Untuk SMA/MA dan SMK/MAK Kelas X” published by Putra Nugraha that covers one semester program of the first grade. The data are in the form of dialogues, passages, monologues, tasks, activities, instructions, tables, and etc. The textbook that is being analyzed contains seven chapters that are elaborated into 64 pages. Research Instruments As a device to collect the data, the research instrument is very important. It is a device to collect the data from the object of the study. As a descriptive qualitative study, the data of this study are in form of words rather than numbers in which the researcher is the main instrument. The main role of the researcher as the instrument in this study is profoundly to collect and analyze the data as deep as possible. However, the researcher cannot work alone. The researcher is assisted by the other research instruments; here is the field note. Others contrast field notes with data, defining field notes more along the lines of Field note is a daily input made in a field journal to record thoughts, impressions, initial ideas, working hypotheses, issues to pursue and so on. Besides, it is also everything collected in the fieldwork —the fieldwork journal, transcripts of conversations and interviews, photographs, audiotapes and videotapes, copies of documents, and artifacts (Schwandt 2007). In this study, the field note is used help the researcher to record the verbal data of the object of the study and verify the conformity of the materials in the textbook and the basic competences of curriculum 2013. The field notes are in form of table which contain the analyzed data and also the evidence of the materials. The first table of field note contains basic competences in the syllabus of curriculum 2013, basic competence in the analyzed textbook and relevant or irrelevant column. Besides, the second table of field note contains basic competences of curriculum 2013, main materials based on the Syllabus of English curriculum 2013, relevant or irrelevant column and the evidence of materials. Data Collection Technique In this study, the technique to collect the data is document analysis based on the checklist. The analysis deals with the conformity between the English learning material and the 2013 English basic competencies. There are two steps that use two tables in this study. The first is the researcher checks the conformity between the basic competences in the textbook to the basic competences in the syllabus of English curriculum 2013. The second is the researcher checks the conformity between the English materials in the textbook to the basic competences of English curriculum 2013. While it is done, the verbal data is also written in the field notes. After those two steps, the researcher collects the data and the result from the instrument table, after that, those data are analyzed and elaborated. Data Analysis Technique Since the English material in the textbook are integrated, the researcher directly describe the results of the study without any skill dividing in form of words rather than numbers. In addition, there are two steps in this study analysis. The first is describing conformity between the basic competences in the analyzed textbook and the basic competences in the syllabus of curriculum 2013. The second is describing the conformity between the materials in the textbook entitled “Bahasa Inggris Untuk SMA/MA dan SMK/MAK Kelas X” published by Putra Nugraha English and the basic competences in the 2013 English curriculum. RESULTS AND DISCUSSION The results of this study are divided into two parts. The first is describing the conformity field note of the basic competences in the textbook for the first grade of senior high school used in SMAN 18 Surabaya entitled “Bahasa Inggris Untuk SMA/MA dan SMK/MAK Kelas X” to the Basic competences in the syllabus of curriculum 2013. The second is describing the conformity field note of the content in the textbook for first graders of senior high school used in SMAN 18 Surabaya entitled “Bahasa Inggris Untuk SMA/MA dan SMK/MAK Kelas X” to the Basic competences in the syllabus of curriculum 2013. The Conformity of the English Basic competences in the textbook to the English Basic Competences in the Syllabus of C urriculum 2013 This part of the results aims to describe the conformity of the basic competences in the textbook for first grader of senior high school used in SMAN 18 Surabaya entitled “Bahasa Inggris Untuk SMA/MA dan SMK/MAK Kelas X” to the basic competences in the syllabus of curriculum 2013. This part is describing the example of field note of Chapter 1 and 2 analyses in which it is described into words to be more specifically explained. The Conformity of the Basic Competences in the Textbook Chapter 1 to the Basic Competences in the Syllabus No. Basic Competence in the Syllabus of Curriculum 2013 Basic Competences in the textbook Conformity 1. 1.1. Mensyukuri kesempatan dapat mempelajari bahasa Inggris sebagai bahasa pengantar Komunikasi internasional yang diwujudkan dalam semangat belajar. 1.1. Mensyukuri kesempatan dapat mempelajari bahasa Inggris sebagai bahasa pengantar Komunikasi internasional yang diwujudkan dalam semangat belajar. relevant 2. 2.2. Menunjukkan perilaku jujur, disiplin, percaya diri, dan bertanggung jawab dalam melaksanakan Komunikasi transaksional dengan guru dan teman. 2.2. Menunjukkan perilaku jujur, disiplin, percaya diri, dan bertanggung jawab dalam melaksanakan Komunikasi transaksional dengan guru dan teman. relevant 3. 3.1. Menganalisis fungsi sosial, struktur teks, dan unsur kebahasaan dari teks pemaparan jati diri, sesuai dengan konteks penggunaannya. 3.1. Menganalisis fungsi sosial, struktur teks, dan unsur kebahasaan dari teks pemaparan jati diri, sesuai dengan konteks penggunaannya. relevant 4. 4.1 Menyusun teks lisan dan tulis sederhana, untuk memaparkan, menanyakan, dan merespon pemaparan jati diri, dengan memperhatikan fungsi sosial, struktur teks, dan unsur kebahasaan, secara benar dan sesuai dengan konteks. 4.1 Menyusun teks lisan dan tulis sederhana, untuk memaparkan, menanyakan, dan merespon pemaparan jati diri, dengan memperhatikan fungsi sosial, struktur teks, dan unsur kebahasaan, secara benar dan sesuai dengan konteks. relevant As can be seen above, all of the Basic competences in chapter 1 are relevant to what they are stated in the syllabus of English curriculum 2013. The basic competences are stated in the beginning of the chapter in the textbook. They are Basic Competences 1.1, 2.2, 3.1 and 4.1. The evidence of this analysis is a picture taken from the analyzed textbook as follows: The Basic Competences in Chapter 1 of the Textbook The picture above shows some basic competences in chapter 1 of the textbook. The basic competences in the textbook above conform to the basic competences in the syllabus as shown in table 4.1. The Conformity of the Basic Competences in the Textbook Chapter 2 to the Basic Competences in the Syllabus No. Basic Competence in the Syllabus of Curriculum 2013 Basic Competences in the textbook Conformity 1. 1.1 Mensyukuri kesempatan dapat mempelajari bahasa Inggris sebagai bahasa pengantar Komunikasi internasional yang diwujudkan dalam semangat belajar. 1.1. Mensyukuri kesempatan dapat mempelajari bahasa Inggris sebagai bahasa pengantar Komunikasi internasional yang diwujudkan dalam semangat belajar. relevant 2. 2.1. Menunjukkan perilaku santun dan peduli dalam melaksanakan Komunikasi interpersonal dengan guru dan teman. 2.1. Menunjukkan perilaku santun dan peduli dalam melaksanakan Komunikasi interpersonal dengan guru dan teman. relevant 3. 3.2. Menganalisis fungsi sosial, struktur teks, dan unsur kebahasaan pada ungkapan memuji bersayap serta responnya, sesuai dengan konteks penggunaannya 3.3. Menganalisis fungsi sosial, struktur teks, dan unsur kebahasaan pada ungkapan memuji bersayap serta responnya, sesuai dengan konteks penggunaannya. relevant 4. 4.2. Menyusun teks lisan dan tulis untuk mengucapkan dan merespon pujian bersayap, dengan memperhatikan fungsi sosial, struktur teks, dan unsur kebahasaan yang benar dan sesuai konteks. 4.2 Menyusun teks lisan dan tulis untuk mengucapkan dan merespon pujian bersayap, dengan memperhatikan fungsi sosial, struktur teks, dan unsur kebahasaan yang benar dan sesuai konteks. relevant Besides, the Filed note above also shows that all of the Basic competences in the chapter 2 are relevant to what they are stated in the syllabus of English curriculum 2013. The basic competences are stated in the beginning of the chapter in the textbook. They are Basic Competences 1.1, 2.1, 3.2 and 4.2. The evidence of this analysis is a picture taken from the analyzed textbook as follows: The Basic Competences in Chapter 2 of the Textbook The picture above shows some basic competences in chapter 2 of the textbook. It can be seen that the basic competences in the textbook above conform to the basic competences in the syllabus as shown in table 4.2. Overall, the study results that all of the basic competences in the textbook for first graders of senior high school used in SMAN 18 Surabaya entitled “Bahasa Inggris Untuk SMA/MA dan SMK/MAK Kelas X” conforms to the basic competences in the syllabus of English Curriculum 2013 (see appendix 1). The conformity of the Materials in the Textbook to the Basic Competences in the Syllabus The textbook entitled “Bahasa Inggris Untuk SMA/MA dan SMK/MAK Kelas X” published by Putra nugraha are claimed as representing the English Curriculum 2013. This book uses thematic and integrated material in delivering four English skills. Since it is integrated, no more skill dividing found in this book. The thematic and integrated material are delivered into seven chapters, they are: I Live in Semarang, Wow! You Look So Pretty, Are You Ok?, I’m Going to…, Congratulations, Simple Past Tense and Simple Present Perfect Tense and Descriptive Text. This part of the study explains and describes the result of the instrument to figure out whether or not materials in the English textbook for first graders of senior high school used in SMAN 18 Surabaya entitled “Bahasa Inggris Untuk SMA/MA dan SMK/MAK Kelas X” conforms to the Basic competences in the Syllabus of Curriculum 2013. The data collection uses table of conformity (see Appendix 2) and the descriptions are divided chapter per chapter. The table analysis of the first and second chapter is presented as the example below: The Conformity of Materials in Chapter 1 to the Basic Competences in the Syllabus NO. Basic Competences in the Syllabus Main Materials Based on the Syllabus Conformity Evidence 1. 1.1. Mensyukuri kesempatan dapat mempelajari bahasa Inggris sebagai bahasa pengantar Komunikasi internasional yang diwujudkan dalam semangat belajar 2.2. Menunjukkan perilaku jujur, disiplin, percaya diri, dan bertanggung jawab dalam melaksanakan Komunikasi transaksional dengan guru dan teman. 3.1. Menganalisis fungsi sosial, struktur teks, dan unsur kebahasaan dari teks pemaparan jati diri, sesuai dengan konteks penggunaannya. 4.1. Menyusun teks lisan dan tulis sederhana, untuk memaparkan, menanyakan, dan merespon pemaparan jati diri, dengan memperhatikan fungsi sosial, struktur teks, dan unsur kebahasaan, secara benar dan sesuai dengan konteks. Simple spoken text to explain self introduction which concerns on right social function, text structure and linguistic element that is appropriate with the context. irrelevant Simple spoken text to ask about self introduction which concerns on right social function, text structure and linguistic element that is appropriate with the context. irrelevant Simple spoken text to respond self introduction which concerns on right social function, text structure and linguistic element that is appropriate with the context. irrelevant Simple written text to explain self introduction which concerns on right social function, text structure and linguistic element that is appropriate with the context. relevant Simple written text to ask about self introduction which concerns on right social function, text structure and linguistic element that is appropriate with the context. irrelevant Simple written text to respond self introduction which concerns on right social function, text structure and linguistic element that is appropriate with the context. irrelevant The table above shows that most of the materials in the textbook do not conform to the basic competences in the syllabus of Curriculum 2013. There is only one material in chapter 1 of the textbook that conform to the basic competences in the syllabus. It is as seen in the picture below. Simple Written Text of self Introduction The picture above shows a simple written text of introduction taken from the analyzed textbook. It conforms to the fourth main material in chapter 1 that represents the basic competences in the syllabus of curriculum 2013. The main material in chapter 1 is Simple written text to explain self introduction which concerns on right social function, text structure and linguistic element that is appropriate with the context. The simple written text of introduction above fulfills the social function, text structure and linguistic element. The text above reflects the social function in which the students are hoped to get into a relationship among others. The text structures are reflected in form of expressions such as “My name is Arai”, and “I am a student in Gemilang senior School”. The last is linguistic element is reflected by the topic about family and brotherhood relationship, hobbies, occupation and the text is using simple present tense. The Conformity of Materials in Chapter 2 to the Basic Competences in the Syllabus NO. Basic Competences in the Syllabus Main Materials Based on the Syllabus Conformity Evidence 1. 1.1. Mensyukuri kesempatan dapat mempelajari bahasa Inggris sebagai bahasa pengantar Komunikasi internasional yang diwujudkan dalam semangat belajar. 2.1. Menunjukkan perilaku santun dan peduli dalam melaksanakan Komunikasi interpersonal dengan guru dan teman. 3.2. Menganalisis fungsi sosial, struktur teks, dan unsur kebahasaan pada ungkapan memuji bersayap serta responnya, sesuai dengan konteks penggunaannya. 4.2. &nb